(untitled) (ModaPalavra e-periódico, 2010)
This paper describes an experimental methodology to create a collection of printed fabrics following specific rules of Gestalt Theory concerning the formation of expressive units. During the design action,there was not a challenge of adapting the goods to any specific fashion market, therefore, the design methodology proved to be relevant at any level of skill in drawing tools (manual or digital),as well as the different themes or styles.